Construction destruction eaudiobook - Dean, James (Pete the Cat., 2015)
Pete the Cat builds a playground in New York Times bestselling artist James Dean's Pete the Cat: Construction Destruction. When Pete sees that the playground is in bad shape, he gets a totally groovy idea—make a new playground! Pete calls in construction workers and cement mixers, backhoes and dump trucks to build the coolest playground ever. In the end, Pete learns that to make something special, you have to dream big. Complete with over 30 stickers!